Clinical characteristics and prognosis of amyopathic dermatomyositis patients with interstitial lung disease: insights from a retrospective cohort - Yanan Ying; Tingting Wu; Long Wang; Yun Zhang; Yiming Yu; Zaichun Deng; Qunli Ding (Orphanet Journal of Rare Diseases)
Abstract Introduction The diagnosis of amyopathic dermatomyositis with interstitial lung disease (ADM-ILD) is challenging due to the lack of typical skin features and overlapping syndromes. We aimed to determine the characteristics and prognosis of patients with ADM-ILD to further guide their clinical management. Methods A retrospective cohort study comprising 190 Chinese patients diagnosed with interstitial lung disease (ILD) was conducted. Patients were stratified into four groups using the Sontheimer criteria and predominant high-resolution computed tomography (HRCT) patterns. Demographic features, clinical presentation, laboratory parameters, duration of ILD, and follow-up data were analysed. Results There were significant differences in the clinical parameters among the 190 patients with ILD in the amyopathic dermatomyositis (ADM, n = 69) and control (n = 121) groups. The ADM with nonspecific interstitial pneumonia (NSIP) group (n = 46) presented increased haemoglobin (125.93 ± 12.91 g/L, p = 0.005), creatine kinase-MB (15.19 ± 8.58 U/L, p < 0.001), and partial pressure of oxygen (93.08 ± 26.20 mmHg, p = 0.003) levels and decreased β2-microglobulin (2.61 ± 1.21 mg/L, p = 0.039) levels compared to the control-NSIP group (n = 92). The ADM with organizing pneumonia (OP) group (n = 23) had a greater percentage of females (7/16, p = 0.023) and higher alanine aminotransferase (30.30 ± 20.67 U/L, p = 0.039) and aspartate aminotransferase (53.35 ± 65.86 U/L, p = 0.003) levels than the control-OP group (n = 29). Both the ADM-NSIP and OP groups presented elevated lactate dehydrogenase (LDH) levels (290.61 ± 86.49 U/L, p = 0.009; 317.35 ± 181.32 U/L, p = 0.003, respectively) and increased anti-nuclear antibody (ANA) positivity rates (82.61%, p = 0.01; 73.91%, p < 0.001, respectively). Notably, 81.26% of patients with ADM-NSIP/OP had LDH levels above normal. The serum LDH levels could be used to distinguish patients with ADM-NSIP/OP (sensitivity: 73.91%, specificity: 82.64%). Survival was shorter among patients with ADM-OP than among control patients (p = 0.002). Cox multivariate analysis revealed that age (p = 0.002), smoking status (p = 0.011), anti-melanoma differentiation-associated gene 5 (MDA5) antibody (p = 0.017), and white blood cell count (p = 0.004) were independent predictors of shorter survival. Conclusions Elevated serum LDH levels in patients predominantly presenting with NSIP or OP patterns may indicate the presence of ADM-ILD. The identified prognostic factors underscore the importance of early detection and personalized management strategies for optimizing outcomes in patients with ADM-ILD.